Respuesta :
Answer:
The value of [tex]\left(\frac{1}{3}+\frac{5}{6}\right)\cdot m[/tex] when [tex]m=\frac{1}{4}[/tex] would be:
[tex]\left(\frac{1}{3}+\frac{5}{6}\right)\frac{1}{4}=\frac{7}{24}[/tex]
Step-by-step explanation:
Considering the expression
[tex]\left(\frac{1}{3}+\frac{5}{6}\right)\cdot m[/tex]
As
- [tex]m=\frac{1}{4}[/tex]
As the expression is
[tex]\left(\frac{1}{3}+\frac{5}{6}\right)\cdot m[/tex]
Putting [tex]m=\frac{1}{4}[/tex] in the given expression would bring:
[tex]\left(\frac{1}{3}+\frac{5}{6}\right)\cdot m[/tex]
[tex]\left(\frac{1}{3}+\frac{5}{6}\right)\frac{1}{4}[/tex]
[tex]\mathrm{Join}\:\frac{1}{3}+\frac{5}{6}:\quad \frac{7}{6}[/tex]
[tex]=\frac{7}{6}\cdot \frac{1}{4}[/tex]
[tex]\mathrm{Multiply\:fractions}:\quad \frac{a}{b}\cdot \frac{c}{d}=\frac{a\:\cdot \:c}{b\:\cdot \:d}[/tex]
[tex]=\frac{7\cdot \:1}{6\cdot \:4}[/tex]
[tex]\mathrm{Multiply\:the\:numbers:}\:7\cdot \:1=7[/tex]
[tex]=\frac{7}{6\cdot \:4}[/tex]
[tex]\mathrm{Multiply\:the\:numbers:}\:6\cdot \:4=24[/tex]
[tex]=\frac{7}{24}[/tex]
Therefore, the value of [tex]\left(\frac{1}{3}+\frac{5}{6}\right)\cdot m[/tex] when [tex]m=\frac{1}{4}[/tex] would be:
[tex]\left(\frac{1}{3}+\frac{5}{6}\right)\frac{1}{4}=\frac{7}{24}[/tex]
Keywords: algebraic expression
Learn more about simplifying algebraic expression from brainly.com/question/4687406
#learnwithBrainly